MAKNA SIMBOLIK KOMUNIKASI BUDAYA DALAM UPACARA ADAT PERKAWINAN MASYARAKAT BATAK TOBA DI PEKANBARU - ", Wahyudi; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The village of Paritbaru subdistrict of Kampar Regency mines the majority of the in habitants are fafmers, livelihoods as edged, which in this case is the oil palm growers, and manage their own land (farmer based organizations). The magnitude of the farmers who rely on the commodity of this palm, of course, be an asset to take advantage and maintained, in an effort to improve the result of the oil palm productions and increase household income in order to improve the export of palm oil, while commodities as an asset is also as a burden and a responsibility for local authoritiesn in order to improve the welfare of the oil palm growers. On the oter sid to see that level of well-being of palm farmers have not sufficient measurable of the personâ€™s needs are met or not. To measure are met or whether there are indicators that became a benchmark: The frequency of maels in a day, have different clothes for different activities, the frequency of buying new clothes at leats once a year, per capita floor area of the house at least 8mÂ², comsumption of meat fis, eggs, at least once a week, kind of toilets/WC, floor type, the availability of clean water, (BKKBN, 2002). To find out the level of welfare of oil palm famers, please note the strategy of survival that became the driving force of the economy in anticipation of oil palm price fluctuations to improve the welfare of the living. 59 the respondents who became the object of research there are 26 respondents lasisified within the family are not prosperous, 10 respondents classifield into families is very prosperous. The strategy nof survival that became the impetus for the level of welfare of live oil palm farmers, namely: active strategies utilized by 2 people passive strategies utilized by respondents 7 people respondents network strategy utilized by 50 respondents.Keywords : Farmer Welfare, Farmer of Oil Palm,Paritbaru Village